Improvement of Personnel Training System in the Conditions of Innovative Development of Agriculture (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses improving the personnel training system in the conditions of innovative development of agriculture. Requirements for personnel are also given for the innovative model of agriculture, capable of creating, maintaining and managing innovative agriculture.